2017
DOI: 10.1159/000485032
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Functioning in Formerly Opioid-Dependent Adults after At Least 1 Year of Abstinence: A Naturalistic Study

Abstract: This study is an evaluation of cognitive functioning in formerly opioid-dependent adults after at least 1 year of abstinence. Participants (45 formerly opioid-dependent patients, referred to as abstainers, and 45 matched healthy controls) completed a structured screening and subsequent cognitive test battery covering intelligence, learning and memory, attention, and executive functions. Many cognitive functions were comparable between long-term abstainers and healthy controls, and we found few relevant differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…They discovered that tramadol users suffer from memory and concentration problems. The findings of the current study were also consistent with the results of the studies demonstrating memory and cognitive impairments in heroin addicts as well as the findings of the studies demonstrating these impairments in abstinent opioid users [ 25 , 26 ].…”
Section: Discussionsupporting
confidence: 91%
“…They discovered that tramadol users suffer from memory and concentration problems. The findings of the current study were also consistent with the results of the studies demonstrating memory and cognitive impairments in heroin addicts as well as the findings of the studies demonstrating these impairments in abstinent opioid users [ 25 , 26 ].…”
Section: Discussionsupporting
confidence: 91%
“…Cognitive deficits in SUD have moderate longevity, and although there is abstinence-related recovery (14)(15)(16), these deficits may significantly complicate treatment efforts during the first 3 to 6 months after discontinuation of drug use. Thus, one of the most critical implications of cognitive deficits for SUD is their potential negative impact on treatment retention and adherence, in addition to clinical outcomes such as craving, relapse, and quality of life.…”
Section: Cognitive Assessmentmentioning
confidence: 99%
“…Opioid use disorder (OUD) is characterized by negative emotional states, as well as cognitive and learning deficits in both children exposed to opioids in utero (Yeoh et al., 2019) and adults (Gruber et al., 2007; Kroll et al., 2018; Schmidt et al., 2017). Human and animal studies have shown that opioid abuse promotes abnormal gray matter volume (Younger et al., 2011), neuronal apoptosis (Bajic et al., 2013; Hu et al., 2002; Mao et al., 2002; Tramullas et al., 2007), oxidative stress (Abdel‐Zaher et al., 2013) and overall changes in neural plasticity (Welsch et al., 2020).…”
Section: Introductionmentioning
confidence: 99%